“We are Performance Philosophy Problems” - Janet Gibson; Kate Maguire-Rosier; Tony McCaffrey (Performance Philosophy)
This article originates from a KeyGroup presentation at the June 2022 Performance Philosophy Problems conference in Helsinki in which the performers of Different Light Theatre Company, a learning-disabled theatre company based in Christchurch, New Zealand, interrogated the conference process, proposing their own research questions for the conference participants as well as questions about theatre, Zoom, and thinking. At the conclusion of the presentation, Laura Cull Ó Maoilearca, asked how ‘we’ (academics and the learning-disabled) can be together in conferences in meaningful and inclusive ways. Two separate pieces form a response to Maoilearca’s question: one from McCaffrey and the other from Maguire-Rosier and Gibson, all participants of the KeyGroup.